How literatures begin : a global history - Lande, Joel B.; Feeney, D. C. (Princeton University Press, 2021)
"The emergence of a literature in any language is an improbable and complex historical achievement. In fact, many known languages throughout history did not develop writing, let alone a literature. This book, a collectively written early history of different literary traditions across the globe and through time, presents a global, comparative account of literary origins spanning the Mediterranean, Asia, Europe, Africa, and the Americas. Seventeen chapters, each written by a scholar with expertise in a particular language and literature, trace the creation of writing and its interaction with oral practices, the rise of print circulation, the passage from sacred to secular writing and reading practices, the use of cultural models, the role of translation, and related issues as they apply to the emergence of literature. The contributions explore the historical context as well as the practices, technologies, and institutions that encouraged the emergence of distinct literatures, from classical Chinese and the resultant establishment of Japanese and Korean traditions, to the advent of Greek, Hebrew, Arabic, and other literatures of the Mediterranean; the birth of European vernaculars against the cosmopolitan backdrop of post-classical Latin; and the later development of African American and Latin American literatures under conditions of colonial expansion and racial oppression. The volume is designed to enable readers to better understand the similarities as well as the differences in the origins of major and enduring literatures across time"--